B cell tolerance and antibody production to the celiac disease autoantigen transglutaminase 2 - Du Pré, M; Blazevski, J; Dewan, A; Stamnaes, J; Kanduri, C; Sandve, G; Johannesen, M; Lindstad, C; Hnida, K; Fugger, L; Melino, G; Qiao, S; et al. (Rockefeller University Press, 2019)
Autoantibodies to transglutaminase 2 (TG2) are hallmarks of celiac disease. To address B cell tolerance and autoantibody formation to TG2, we generated immunoglobulin knock-in (Ig KI) mice that express a prototypical celiac patient-derived anti-TG2 B cell receptor equally reactive to human and mouse TG2. We studied B cell development in the presence/absence of autoantigen by crossing the Ig KI mice to Tgm2 -/- mice. Autoreactive B cells in Tgm2 +/+ mice were indistinguishable from their naive counterparts in Tgm2 -/- mice with no signs of clonal deletion, receptor editing, or B cell anergy. The autoreactive B cells appeared ignorant to their antigen, and they produced autoantibodies when provided T cell help. The findings lend credence to a model of celiac disease where gluten-reactive T cells provide help to autoreactive TG2-specific B cells by involvement of gluten-TG2 complexes, and they outline a general mechanism of autoimmunity with autoantibodies being produced by ignorant B cells on provision of T cell help.